2010
DOI: 10.3945/ajcn.2010.29686
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of the effect of zinc supplementation on the mental health of school-age children in Guatemala

Abstract: Six months of zinc supplementation did not induce differences in mental health outcomes between zinc and placebo groups. However, increases in serum zinc concentrations were associated with decreases in internalizing symptoms (ie, depression and anxiety) in a community-based sample of children at risk of zinc deficiency. This trial was registered at clinicaltrials.gov as NCT00283660.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Intervention trials have shown that zinc supplementation can improve neurological and psychological development in undernourished children (Bentley et al 1997; Bhutta et al 1999; Brown et al 2002; Gardner et al 2005; Penland et al 1997; Sazawal et al 2001). However, some studies have also reported null (DiGirolamo et al 2010), or even negative effects of zinc supplementation on children’s cognitive development (Hamadani et al 2001; Hamadani et al 2002). Some children may benefit from supplementation more than others making it difficult for these trials to reach statistical significance.…”
Section: Zinc Deficiency Erk1/2 and Behaviormentioning
confidence: 99%
“…Intervention trials have shown that zinc supplementation can improve neurological and psychological development in undernourished children (Bentley et al 1997; Bhutta et al 1999; Brown et al 2002; Gardner et al 2005; Penland et al 1997; Sazawal et al 2001). However, some studies have also reported null (DiGirolamo et al 2010), or even negative effects of zinc supplementation on children’s cognitive development (Hamadani et al 2001; Hamadani et al 2002). Some children may benefit from supplementation more than others making it difficult for these trials to reach statistical significance.…”
Section: Zinc Deficiency Erk1/2 and Behaviormentioning
confidence: 99%
“…However, recent RCTs have failed to demonstrate a benefit for either iron or zinc supplementation over placebo [53,60,61]. All but one recent RCTs on elimination diets did not generate recommendations for them being a generally applicable treatment for children who have ADHD [65,66 ].…”
Section: Resultsmentioning
confidence: 98%
“…Of note, a caloric spectrophotometer was used instead of an atomic absorption spectrophotometer due to the limited budget of the study. DiGirolamo et al [61] conducted a 6-month randomized, double-blind, controlled trial comparing zinc supplementation with a placebo (glucose) in 674 Guatemalan children in grades 1-4. The groups given zinc and placebo did not differ significantly in any behavioral measures at baseline or at follow-up: this included parent-reported scores for their children's behavioral problems.…”
Section: Zinc Supplementationmentioning
confidence: 98%
“…Furthermore, zinc treatment was reported significantly superior to placebo in reducing symptoms of hyperactivity, impulsivity and impaired socialization in ADHD patients [58,59]. Another preliminary human study showed that many children with ADHD have lower zinc concentration in comparison to healthy children and zinc supplement as an adjunct to methylphenidate has favourable effects in the treatment of ADHD children, pointing to the possible association of zinc deficiency and ADHD pathophysiology [60].…”
Section: Discussionmentioning
confidence: 99%